Peran Pemimpin terhadap Perubahan Sistem Ekonomi Menuju Indonesia Maju - Manurung, Aprina Septauli; Putri, Devi Adinda; Nasution, Armin Rahmansyah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to analyze the role of leaders in changing the economic system towards an advanced Indonesia. This research will use a qualitative approach with a case study method. The qualitative approach was chosen because it allows for in-depth information and meaning about the role of leaders in economic system change, which cannot be captured by quantitative methods. The findings of this research provide a deep insight into the role played by President Joko Widodo in driving change in Indonesia's economic system towards a more advanced Indonesia. Through careful analysis of the data, it can be concluded that strong leadership, clear vision, high commitment to economic development, and the ability to build consensus have been key factors in Jokowi's success.